The inverse of the function is [tex]f^{-1}(x)=\frac{1}{5}x[/tex]
Explanation:
The given function is [tex]f(x)=5x[/tex]
We need to determine the inverse of the function [tex]f^{-1}(x)[/tex]
The inverse of the function can be determined by interchanging the variables x and y.
Let us interchange the variables x and y in the function [tex]f(x)=5x[/tex], we have,
[tex]x=5y[/tex]
To find the inverse of the function, let us solve for y.
Hence, dividing both sides of the equation by 5, we get,
[tex]\frac{1}{5}x=y[/tex]
This is the inverse of the function [tex]f(x)=5x[/tex]
Therefore, the inverse of the function is [tex]f^{-1}(x)=\frac{1}{5}x[/tex]